2010
DOI: 10.5009/gnl.2010.4.2.192
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Sequential Capsule Endoscopy Using MiroCam and PillCam SB Devices with Different Transmission Technologies

Abstract: Sequential capsule endoscopy with the MiroCam and PillCam SB produced slight but nonsignificant increases in the diagnostic yield, and the two capsules did not exhibit electrical interference. A larger trial is necessary for elucidating the usefulness of sequential capsule endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 20 publications
4
19
1
2
Order By: Relevance
“…In each case, both capsules were retained and thus, it is uncertain if the MC had been the lead capsule in these cases whether the MC would have been retained as well. Two prior published studies involving MC demonstrated no cases of MC capsule retention 3,11 . Although some of this may be as a direct result of fortuitous patient selection or small sample sizes in these prior studies, one putative explanation may be the smaller external dimensions of the MC capsule compared to the PC (Table 2).…”
mentioning
confidence: 99%
“…In each case, both capsules were retained and thus, it is uncertain if the MC had been the lead capsule in these cases whether the MC would have been retained as well. Two prior published studies involving MC demonstrated no cases of MC capsule retention 3,11 . Although some of this may be as a direct result of fortuitous patient selection or small sample sizes in these prior studies, one putative explanation may be the smaller external dimensions of the MC capsule compared to the PC (Table 2).…”
mentioning
confidence: 99%
“…The pilot study of sequential capsule endoscopies using MiroCam and PillCam showed complete examination rate 83.3 % in MiroCam and 58.3 % in PillCam (p = 0.031) [68]. Diagnostic yields for MiroCam and PillCam were 45.8 % and 41.7 % (p [ 0.05), respectively.…”
Section: Comparative Studies With the Conventional Capsule Endoscopesmentioning
confidence: 98%
“…Secondly, the CMOS image sensor was designed to minimize power consumption, and thirdly, the telemetry chip and image sensor were combined on one chip to reduce the current required for fan-out between chips. With this advantage, the capsule operation time prolonged up to 11 h only with two usual silver oxide batteries, and thereby, MiroCam improves the complete ratio to explore the entire small bowel [68].…”
Section: Advantages Of Mirocammentioning
confidence: 99%
“…The video images (60,000-100,000 pixels per one image) are taken at 2-3 frames per second and transmitted to the data recorder on patient's belt, so about 50,000 images are stored for 8-11 hours of battery life, transferred to computer, and interpreted. There is no difference of the diagnostic yield between two capsule endoscopes available in Korea [10].…”
Section: Types Of Capsule Endoscopementioning
confidence: 99%